STUDENTS AWARENESS OF PLAGIARISM IN PARAPHRASING ENGLISH TEXT - Sarair; Inas Astila; Yuniarti (Getsempena English Education Journal, 2019)
This study was conducted to find out the students awareness of plagiarism while they’re paraphrasing the English text. Researchers took 30 samples from private universities namely Universitas Muhammadiyah Aceh and the state university UIN Ar-Raniri Banda Aceh. This study uses questionnaire to investigate this research which contain 13 questions. The result of this study shows that more than seventy percent of the samples taken by researchers understand what paraphrase and what plagiarism are. However they still faced some problems how to avoid plagiarism in their writing. 10 percent of the students said in order to avoid plagiarism is by providing references even in their personal notes, 16,7 percent said that when using the ideas of others, it must clear who the original author was, then 33,3 percent said that to avoid plagiarism is only by writing notes in their own words and the last 40 percent of the students choose all the answers to answer all the way to avoid plagiarism.